(untitled) (Stato, Chiese e pluralismo confessionale, 2012)
Testo, corredato con note essenziali, della relazione svolta al convegno di studi in onore di Giorgio Peyrot “Il Giurista delle minoranze religiose”, tenutosi a Genova, 8–9 aprile 2011, i cui Atti sono di prossima pubblicazione SOMMARIO: 1. Il contributo di Giorgio Peyrot alla definizione delle intese – 2. Il suo impegno per l’attuazione delle intese – 3. La crisi dell’istituto… – 4. … e le sue ragioni: a) il passaggio alla società multi religiosa – 5. (Segue): b) la noncuranza della Costituzione – 6. Limiti e attualità del pensiero di Giorgio Peyrot sulle intese. ABSTRACT Giorgio Peyrot, one of the most eminent scholars of law and religions in Italy, was very committed, also as representative of the waldensian Church – therefore they called him “the jurist of the minorities” -, in the long struggle for the implementation of the “intese”, i.e. of the conventions between the state and the various religious fellowships different from the catholic Church. Yet, after the aim was acheaved at least in respect of a few communities, then the crisis of this legal institution began: first of all, for the transition to a multicultural and multireligious society, that faces the West with new and not traditional communities, and moreover for the disregard for the Constitution and its institutions, that especially, but not only, the italian Center-Right is spreading throughout Italy. This paper shows the limits and nevertheless the topicality of the legal thought of Peyrot about the “intese” in the context of these times.